2016
DOI: 10.2139/ssrn.2910308
|View full text |Cite
|
Sign up to set email alerts
|

The Implications of Book-Tax Differences: A Meta-Analysis

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
(111 reference statements)
0
6
0
Order By: Relevance
“…Relatedly, we capture firms' tax avoidance by predicted tax benefits (e.g., Rego and Wilson 2012) and book-tax-differences (e.g., Wilson 2009). We acknowledge that there is inconsistent evidence on whether book-tax-differences indicate opportunistic reporting (see Evers et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Relatedly, we capture firms' tax avoidance by predicted tax benefits (e.g., Rego and Wilson 2012) and book-tax-differences (e.g., Wilson 2009). We acknowledge that there is inconsistent evidence on whether book-tax-differences indicate opportunistic reporting (see Evers et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…More again, leverage and operating lease expenses tend to be negatively associated with the effective tax rate. Evers et al (2016) assessed the implications of tax aggressiveness on firms' opportunistic behaviour via meta-regression. Results indicated that tax aggressiveness suggests opportunistic reporting behaviour and even more so of earnings management.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…We based on the same assumption as e.g. [9,17,18] that BTDs are indeed indicative of opportunistic reporting behaviour, and even more so of earnings management. Tang states that BTDs are a useful indicator of earnings and tax management after accounting for the mechanical differences due to the divergent reporting rules for book and tax purposes.…”
mentioning
confidence: 99%
“…There is a substantial diversity with respect to the measurement of BTDs as well as with regard to the definition of the proxies. [17] For the needs of our study, we decided to use the total BTDs (TBTDs) as suggested [21]. TBTDs represent the most comprehensive measure and capture both temporary and permanent BTDs.…”
mentioning
confidence: 99%
See 1 more Smart Citation